INTRODUCTION TO INTERNATIONAL CRIMINAL LAW - Nobuo Hayashi (Fakultas Hukum Universitas Trisakti, 2008)
In discourse of international criminal law, today, individual criminal responsibility is an important principle. This principle will be explained along with other aspects, such as